2021
DOI: 10.3390/jcm10163698
|View full text |Cite
|
Sign up to set email alerts
|

Low Muscle Mass in Patients Receiving Hemodialysis: Correlations with Vascular Calcification and Vascular Access Failure

Abstract: Background: Sarcopenia involves an age-related decline in skeletal muscle mass with functional disability or low muscle strength. Vascular calcification (VC) occurs commonly in patients with chronic kidney disease, in whom it is associated with cardiovascular disease. We aimed to investigate the correlations of low muscle mass with the quantified vascular calcification score (VCS) of the arm of vascular access, as well as whether low muscle mass is associated with the incidence of vascular access failure. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Several studies have shown a relationship between CVD and reduced muscle mass in young and old people [ 116 ]. Some studies linked muscle mass loss with vascular calcifications [ 117 ]. In the Melbourne Collaborative Cohort study, older women with severe abdominal aortic calcification showed a decline in handgrip strength [ 10 ].…”
Section: Aging-related Changes In Skeletal Muscle and Cardiovascular ...mentioning
confidence: 99%
“…Several studies have shown a relationship between CVD and reduced muscle mass in young and old people [ 116 ]. Some studies linked muscle mass loss with vascular calcifications [ 117 ]. In the Melbourne Collaborative Cohort study, older women with severe abdominal aortic calcification showed a decline in handgrip strength [ 10 ].…”
Section: Aging-related Changes In Skeletal Muscle and Cardiovascular ...mentioning
confidence: 99%
“…[17] Tere is disagreement between studies as to whether BIA-derived LMM and sarcopenia is [6,18] or is not [19][20][21] more common in males than females on haemodialysis, though studies observing no signifcant diference may have lacked power. Other studies have defned LMM/sarcopenia from within-cohort medians rather than from healthy young adults as per European Working group on Sarcopenia in Older People (EWGSOP) guidelines [5,22,23].…”
Section: Introductionmentioning
confidence: 99%